(untitled) (Research, Society and Development, 2024)
Introduction: In Antiretroviral Therapy, adherence to the proposed pharmacotherapeutic treatment is of fundamental importance to guarantee the viral suppression of HIV, increasing longevity and guaranteeing quality of life for people living with HIV/AIDS. Objective: To map the main factors that influence adherence to pharmacotherapeutic treatment for HIV/AIDS; as well as the strategies used to achieve adherence. Methodology: Scope review guided by the acronym PCC in which: Participants: people living with HIV/AIDS; Concept: non-adherence to Antiretroviral Therapy; Context: Health services. Results: 15 articles were retrieved, which demonstrate the most common reasons for non-adherence and the importance of using strategies to improve adherence. Conclusion: Evidence was found that the use of strategies for adherence to Antiretroviral Therapy are effective in the pharmacotherapeutic treatment of HIV/AIDS.